2019
DOI: 10.3892/ijo.2019.4744
|View full text |Cite
|
Sign up to set email alerts
|

Solamargine inhibits gastric cancer progression by regulating the expression of lncNEAT1_2 via the MAPK signaling pathway

Abstract: Solamargine, a derivative from the steroidal solasodine in Solanum species, has exhibited anticancer activities in numerous types of cancer; however, its role in gastric cancer (GC) remains unknown. In the present study, it was demonstrated that Solamargine suppressed the viability of five gastric cancer cell lines in a dose-dependent manner and induced notable alterations in morphology. Treatment with Solamargine promoted cell apoptosis (P<0.01). Solamargine increased the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 46 publications
1
47
0
Order By: Relevance
“…In glioblastoma, studies have found that abnormal expression of C20orf166-AS1 leads to a decrease in survival time in patients with glioblastoma. 14,34,35 Related studies have found that the invasion and metastasis of gastric cancer cells are closely related to T A B L E 2 In the degree centrality, betweenness centrality, and closeness centrality rank the top 10 genes 33 In the C20orf166-AS1 regulatory network ( Figure 5A), there were six miRNAs and 105 mRNAs interacting with C20orf166-AS1.…”
Section: Relationship Between Lncrnamentioning
confidence: 96%
See 1 more Smart Citation
“…In glioblastoma, studies have found that abnormal expression of C20orf166-AS1 leads to a decrease in survival time in patients with glioblastoma. 14,34,35 Related studies have found that the invasion and metastasis of gastric cancer cells are closely related to T A B L E 2 In the degree centrality, betweenness centrality, and closeness centrality rank the top 10 genes 33 In the C20orf166-AS1 regulatory network ( Figure 5A), there were six miRNAs and 105 mRNAs interacting with C20orf166-AS1.…”
Section: Relationship Between Lncrnamentioning
confidence: 96%
“…Some studies have found that MAPK signaling pathway plays a key role in gastric cancer cells. 14,34,35 Related studies have found that the invasion and metastasis of gastric cancer cells are closely related to T A B L E 2 In the degree centrality, betweenness centrality, and closeness centrality rank the top 10 genes 36 Meanwhile, it is reported that cross-linked hyaluronic acid gel for preventing postoperative abdominal adhesion may inhibit MAPK/ ERK induced by epidermal growth factor (EGF), PI3K-Akt and Rac1 mediated signaling pathways have antitumor effects on gastric cancer. 37 In this study, we found that CACNA1H, FLNA, and FLNC were abnormally expressed in the MAPK signaling pathway, which provided a reference for further understanding the pathogenesis of gastric cancer.…”
Section: C20orf166-as1 Related Regulatory Network and Gastric Cancermentioning
confidence: 99%
“…We believed that the SM doses used in this study were reasonable and feasible which based on our and other studies (Chen, Tang, Xiao, Yang & Hann, 2017;Fu et al, 2019;Tang, Zheng, Wu, Xiao, Li & Hann, 2017). Regardless, more experiments and statistical analysis are required to further determine the critical role and correlations of CCAT1, miR7-5p and SP1, and tumor sizes in this process in mice model.…”
Section: Discussionmentioning
confidence: 73%
“…Dynamic changes in NEAT1 lncRNA levels are involved in tumorigenesis, where the ratio of NEAT1_1 to NEAT1_2 may be important. Various studies show NEAT1_1 primarily has a cell-proliferative role in cancer cells [18-21], whereas NEAT1_2 appearance can be associated with both tumour-suppressive and oncogenic activity [21-25]. In cancer, as well as other biological contexts, the overall transcription of NEAT1 is increased with stressors such as hypoxia, heat shock, mitochondrial stress and proteasome inhibition [26-28,18], driven by a number of upstream factors, including p53 [23,24].…”
Section: Introductionmentioning
confidence: 99%